Speech Acts in ILC (Indonesia Lawyers Club) Talk Show Program - Lisna Rifkadiana S; Busmin . Gurning; T. Thyrhaya Zein (Universitas Negeri Medan, 2021)
This study was concerned with the use of speech acts in ILC (Indonesia Lawyers Club) Talk show program. The objective of this study was to describe the types of speech acts used by the host and the guests of ILC. Qualitative content analysis method was applied in this study. The sources of data were the host and the guests in ILC. The data of the study were the sentences and the phrases gathered from the conversation in the episodes of ILC. The finding of this study showed that four types of speech acts, namely rex`x` presentative, directive, commissive, and expressive were used by the host and the guests of ILC, while declarative speech act was not found at all in the episodes of that talk show program. The dominant type of speech act used by the host was directive, while the guests dominantly used representative speech act. Keywords: Speech Acts, Indonesia Lawyers Club, Talk Show Program. Conversation